SOLPS-ITER Study of neutral leakage and drift effects on the alcator C-Mod divertor plasma. (August 2017) - Dekeyser, W.; Bonnin, X.; Lisgo, S.W.; Pitts, R.A.; Brunner, Dan; LaBombard, Brian; Terry, Jim L.
Highlights: First fully coupled SOLPS-ITER simulations of the Alcator C-Mod divertor plasma including kinetic neutrals and drifts. Neutral leakage through divertor sub-structure strongly impacts divertor conditions. Drift flows through private flux region strongly impact inner and outer target recycling conditions and asymmetries. Abstract: As part of an effort to validate the edge plasma model in the SOLPS-ITER code suite under ITER-relevant divertor plasma and neutral conditions, we report on progress in the modeling of the Alcator C-Mod divertor plasma with the new code. We perform simulations with a complete drifts model and kinetic neutrals, including effects of neutral viscosity, ion-molecule collisions and Ly α -opaque conditions, but assuming a pure deuterium plasma. Through a series of simulations with varying divertor geometries, we show the importance of including neutal leakage paths through the divertor substructure on the divertor plasma solution. Moreover, the impact of drifts on inner-outer target asymmetries is assessed. Including both effects, we achieve excellent agreement between simulations and upstream and outer target Langmuir Probe data. In absence of strong volumetric losses due to e.g. impurity radiation in our simulations, the strong inner target detachment observed experimentally remains elusive in our modeling at present.